Design and control of a soft robotic arm - Zhang, Bojian (Nanyang Technological University, 2022)
This dissertation presents a novel soft robotic material-based gripper which is controlled by tendon driven system. One of significant characteristic of the gripper is stiffness changing ability. The soft robotic material constructs a kind of structured fabric which looks like chain mail. In unvacuumed situation, the components of fabric have no interlock which creates flexibility of gripper. Once applying vacuumed situation, the particles interlock, the chain mail jam, and gripper harden. The dissertation describes the concept, the snake-shaped gripper, and the control system design.